Early restoration of immune and vascular phenotypes in systemic lupus erythematosus and rheumatoid arthritis patients after B cell depletion. Issue 9 (26th July 2019) - Pérez‐Sánchez, Carlos; Cecchi, Irene; Barbarroja, Nuria; Patiño‐Trives, Alejandra M.; Luque‐Tévar, María; Pérez‐Sánchez, Laura; Ibáñez‐Costa, Alejandro; Arias de la Rosa, Iván; Ortega, Rafaela; Escudero, Alejandro; Castro, María Carmen; Radin, Massimo; et al.
Abstract: This translational multi‐centre study explored early changes in serologic variables following B lymphocyte depletion by rituximab (RTX) treatment in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) patients and investigated in vitro effects on the activity of other immune cells and the vascular endothelium. Eighty‐five SLE patients, seventy‐five RA patients and ninety healthy donors were enrolled. Two additional cohorts of selected SLE and RA patients were treated with RTX for 3 months. Changes in circulating levels of inflammatory mediators, oxidative stress markers and NETosis‐derived bioproducts were evaluated. Serum miRNomes were identified by next‐generation sequencing, and RTX‐induced changes were delineated. Mechanistic in vitro studies were performed to assess activity profiles. Altered inflammatory, oxidative and NETosis‐derived biomolecules were found in SLE and RA patients, closely interconnected and associated to specific miRNA profiles. RTX treatment reduced SLE and RA patients' disease activity, linked to a prominent alteration in those biomolecules and the reversal of altered regulating miRNAs. In vitro studies showed inhibition of NETosis and decline of pro‐inflammatory profiles of leucocytes and human umbilical vein endothelial cells (HUVECs) after B cell depletion. This study provides evidence supporting an early RTX‐induced re‐setting of the pro‐inflammatory status in SLE and RA, involving a re‐establishment of the homeostatic equilibrium in immune system and the vascular wall.